Ethnographic Theology: Integrating the Social Sciences and Theological Reflection - Gerardo Martí (Cuestiones Teológicas)
Theologians are widely embracing ethnographic research to accomplish their theological work. However, since most theologians are not substantively trained in social scientific methods, their sophistication with this methodology is limited, leading to distortions in recorded observations and proffered interpretations. This essay seeks to address this lack of depth by articulating some of the most essential sensitivities that are crucial to the best practices associated with exemplary scholarship emerging at the intersection of ethnography and theology. Among the most important distinctions that theologians must recognize is a simple, heuristic distinction between “found theologies” and “imposed theologies”. Ethnographers know that reporting our findings always requires a careful examination of the assumptions that may unwittingly constrain what we recognize, let alone “see.” The distinction offered between “found theologies” and “imposed theologies” serves to remind theologically concerned field workers that unexamined ideals and prejudices as well as deeply held values and convictions can radically direct our attention and creatively reshape our perceptions. It also allows insightful focus on the dynamics of power as well as inclusion of marginalized peoples. My modest goal, therefore, is to further equip theologically-oriented scholars to produce original, social-scientifically conscientious, yet substantively rich and responsible works that further innovate the use of social science methodology among theologians. Ultimately, by further substantiating the ethics of ethnographic practice among theologians, students and scholars will accentuate the integrity of findings and produce streams of scholarship that will foster the unexpected and urgently needed theologies of the future.